2007
DOI: 10.1007/s00464-006-9086-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic radical cystectomy: an Italian survey

Abstract: The LRC procedure is feasible although technically demanding. The morbidity of this procedure is evident, but may be reduced with further experience. Bowel management and reconstruction remain the most challenging part of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Prolonged contact of urine with the bowel mucosa causes metabolic disturbances secondary to electrolyte reabsorption, typically a hypercholoremic metabolic acidosis (Chang et al 2000). Excessive production of mucus by bowel mucosa may impair bladder emptying or cause catheter plugging, put patients at risk for bladder rupture (SighinolW et al 2007) and stone formation (Abreu et al 2005). Additionally, carcinogenesis risk in bowel urinary diversion is increased possibly due to nitrosamine production (Filmer et al 1990).…”
Section: Discussionmentioning
confidence: 97%
“…Prolonged contact of urine with the bowel mucosa causes metabolic disturbances secondary to electrolyte reabsorption, typically a hypercholoremic metabolic acidosis (Chang et al 2000). Excessive production of mucus by bowel mucosa may impair bladder emptying or cause catheter plugging, put patients at risk for bladder rupture (SighinolW et al 2007) and stone formation (Abreu et al 2005). Additionally, carcinogenesis risk in bowel urinary diversion is increased possibly due to nitrosamine production (Filmer et al 1990).…”
Section: Discussionmentioning
confidence: 97%
“…All articles excluded were due to either non-relevance to the aim of this review or reported on less than 50 LRC. Seven articles were included, their results are depicted on Table-4 (10)(11)(12)(13)(14)(15)(16)(17). No studies were found describing the learning curve for laparoscopic cystectomy procedures.…”
Section: Literature Searchmentioning
confidence: 99%
“…Castillo et al, have the second largest series with 85 LRC (24 conduits, 42 neobladders, 10 Indiana pouches, 9 Mainz II pouches), followed by Cathelineau et al with 84 LRC (33 conduits and 51 neobladders) and Sighniolfi et al with 83 LRC (43 conduits and 26 neobladders) [4, 7, 11]. None of these studies compared the types of urinary diversions.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, RC is performed by an open surgical technique; however, more recently, a minimally invasive approach has been established in numerous centres across the world [3, 7]. In fact, with the advancement of laparoscopy equipment and the increased skills of urologists performing minimally invasive surgery, laparoscopic radical cystectomy (LRC) has become a viable alternative to open radical cystectomy (ORC).…”
Section: Introductionmentioning
confidence: 99%